Three new endemic Aphyosemion species (Cyprinodontiformes: Nothobranchiidae) from the Massif du Chaillu in the upper Louessé River system, Republic of the Congo - Zee, Jouke R. Van Der; Walsh, Gina; Mikembi, Valdie N. Boukaka; Jonker, Michiel N.; Alexandre, Marco P.; Sonnenberg, Rainer (Zootaxa, 2018)
Three new ‘Aphyosemion’ species are described from the upper Louessé River in the Massif du Chaillu, Republic of the Congo, based on a combination of DNA, habitat preference, male colour pattern, and morphological data. ‘Aphyosemion’ cyanoflavum, new species, is a member of the ‘A’. ogoense group. It differs from its congeners by a unique colour pattern and cephalic sensory system which contains a wide supra-orbital groove with large, densely pigmented anterior neuromasts and dark frontal neuromasts housed in one pit with one central anterior lobe. ‘Aphyosemion’ mandoroense, new species, and ‘A’. cryptum, new species, are members of the ‘A’. coeleste group. ‘Aphyosemion’ cryptum, new species, is in appearance very similar to ‘A’. coeleste, but lacks the typical post opercular metallic green blotch and is generally larger in body size. Initial DNA analyses demonstrate that ‘A’. cryptum, new species, is more closely related to ‘A’. mandoroense, new species, than to ‘A’. coeleste, despite similarity in appearance. ‘Aphyosemion’ cryptum, new species, and ‘A’. coeleste occur syntopic in several locations in a sub-catchment of the upper Louessé system, however differ in microhabitat preference. ‘Aphyosemion’ mandoroense, new species, differs by male body and fin colour pattern from all species of the ‘A’. coeleste group except ‘A’. citrineipinnis. From the latter, it can be distinguished by the absence of red pigmentation and a dark grey to black margin in the unpaired fins.